(untitled) (International Journal of Industrial Engineering and Construction Management (IJIECM), 2023)
The construction industry faces persistent challenges in ensuring transparency, efficiency, and security in project management. This paper explores the application of blockchain technology to address these issues, proposing a framework that leverages blockchain’s decentralized, immutable ledger capabilities to enhance construction project management. By utilizing smart contracts, blockchain can automate processes, reduce administrative overhead, and improve accountability. The framework also incorporates real-time monitoring and secure data sharing, ensuring all stakeholders have access to accurate and up-to-date information. Case studies demonstrate the effectiveness of blockchain in streamlining supply chain management, mitigating risks, and fostering greater trust among project participants. The findings highlight the transformative potential of blockchain technology in construction, offering a robust solution for improving transparency, efficiency, and stakeholder collaboration. This research provides valuable insights into the practical applications of blockchain, paving the way for innovation in construction project management.